Motivating systems‐oriented research on environmental and policy changes for obesity prevention. Issue 3 (6th April 2016) - Cheskin, L. J.; Frutchey, R.; McDermott, A. Y.; Esposito, L.; Lee, B. Y.; Kumanyika, S.
Summary: Background: Research on the types of interventions needed for population‐level prevention of childhood obesity in complex societal systems can benefit from greater use of systems‐science concepts and tools. Objectives: We report outcomes of a funding programme promoting incorporation of systems‐science approaches into studies of imminent policy or environmental changes potentially impacting childhood obesity. Methods: Seven funding cycles over 3 years yielded 172 initial submissions from 29 US states and 25 other countries were analyzed. Results: Submissions focused primarily on aspects of school or child‐care settings, parks and recreational settings, or access to healthy food; about half reflected attention to systems perspectives. Conclusions: Analysis of initial submissions as well as the 15 funded projects showed some success in motivating use of systems concepts and tools but suggested the need for a more focused effort to educate and prepare the childhood obesity prevention research community for this potentially crucial type of research.